Facile indazole-endowed thiadiazole hybrid derivatives as antibacterial, anti-diabetic and thymidine phosphorylase inhibitors: An insight to experimental, in-vitro biological potential and computational approaches - Sabeen Arshad; Aneela Maalik; Wajid Rehman; Yousaf Khan; Mohammed M. Alanazi; Hina Sarfraz; Liaqat Rasheed (Saudi Pharmaceutical Journal)
Abstract In this study, a series of newly synthesized indazole-based thiadiazole hybrid derivatives (1–13) were successfully synthesized from indazole-based thiosemicarbazides starting from the 5-methyl-1H-indazole-3-carboxylic acid. The structure of the synthesized compounds were confirmed through different spectroscopic techniques i.e. FT-IR, 1HNMR, 13CNMR and HRMS. Furthermore, the biological potency of the synthesized indazole based thiadiazole scaffolds were assessed through in-vitro screening against thymidine phosphorylase and α-glucosidase enzymes. The biological potential of the synthesized derivatives was found to be influenced by the size, nature and position of substituents on the hybrid scaffold. Some derivatives displayed significant inhibitory activity, with some exhibiting superior potency compared to standard reference drugs. Moreover, the inhibitory potential of the derivatives were compared with standard 7-Deazaxanthine (7DX) and acarbose. Notably, derivatives 1, 2, 3, 5, 7, and 8 demonstrated remarkable inhibitory activity against thymidine phosphorylase and α-glucosidase, respectively. In addition, based on docking studies, the synthesized indazole-based thiadiazole scaffolds showed good binding interactions with different amino acids. Comparing the analogs' binding affinities and molecular interactions with standard reference drugs revealed favorable mechanisms. Similarly, an ADMET analysis was performed on the synthesized derivatives in order to predict their pharmacokinetics and drug-like characteristics. Using ADMET profiler, it was determined that the derivatives possessed drug-like properties. As a result of this study, indazole based thiadiazole hybrid derivatives have been designed, synthesized, and biologically evaluated as potent dual inhibitors of thymidine phosphorylase and α-glucosidase. These scaffolds display significant inhibitory potential, which were further analysed by docking and ADMET studies, emphasizing their potential as potent compounds for the development of new therapeutic agents that target these enzymes.